2012
DOI: 10.1016/j.ypmed.2012.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of periconceptional folic acid supplementation among Nepalese women of childbearing age: a cross-sectional study

Abstract: Knowledge of FAS is very low among women of childbearing age in Kathmandu. Inclusion of FAS information in health awareness programs is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
8
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 18 publications
6
8
1
2
Order By: Relevance
“…These findings provide a snapshot of the level of folic acid fortified flour intake among WRA after initiation of a fortification program in Ifakara. Folic acid awareness was low, far less than awareness reported in other studies done in Nepal, Honduras, Europe, USA, and New Zealand where awareness ranged from 40 to 98% [10][11][12][13][14]. Furthermore, our study found that only five (10.1%) respondents who were aware of folic acid knew that folic acid can prevent some birth defects.…”
Section: Discussioncontrasting
confidence: 86%
“…These findings provide a snapshot of the level of folic acid fortified flour intake among WRA after initiation of a fortification program in Ifakara. Folic acid awareness was low, far less than awareness reported in other studies done in Nepal, Honduras, Europe, USA, and New Zealand where awareness ranged from 40 to 98% [10][11][12][13][14]. Furthermore, our study found that only five (10.1%) respondents who were aware of folic acid knew that folic acid can prevent some birth defects.…”
Section: Discussioncontrasting
confidence: 86%
“…A recent systematic review [ 41 ] demonstrated that even in high income countries, only half of all women use folic acid before conception, therefore protective levels cannot be achieved before the critical period of neural tube closure. Reasons for low prevalence of use are confirmed by other studies [ 220 - 228 ] and include low maternal education and socioeconomic status; young maternal age; lack of a partner; and unplanned pregnancy. It is necessary therefore to improve awareness and use of folic acid supplements among all women of reproductive age so that even women with unplanned pregnancies are protected.…”
Section: Discussionsupporting
confidence: 64%
“…Low awareness in action of folic acid is supported by study done in Kathmandu model hospital by Paudel, Wing & Silpakar that study result showed that awareness in folic acid supplementation is very low. 13 However other studies showed that slightly more awareness; there was 49.7% in study done in China by Liang, Ma, Zhou, & Li and 59% in study done by Delgado. 14,15 As regard the association between level of awareness and sex of respondents, the study findings revealed that there is no statistically significant relationship between awareness level and sex of the respondents.…”
Section: Discussionmentioning
confidence: 92%